EQ-5D full health state after therapy heralds reduced hazard to accrue subsequent organ damage in systemic lupus erythematosus - Lindblom, Julius; Zetterberg, Sture; Emamikia, Sharzad; Borg, Alexander; von Perner, Gunilla; Enman, Yvonne; Heintz, Emelie; Regardt, Malin; Grannas, David; Gomez, Alvaro; Parodis, Ioannis (Frontiers in Medicine, 2022)
Objectives To investigate whether self-reported EQ-5D full health state (FHS) after therapeutic intervention for active systemic lupus erythematosus (SLE) is associated with a reduced risk to accrue organ damage. In a separate analysis, we sought to investigate associations between experience of “no problems” in each one of the five dimensions of EQ-5D and the risk to accrue damage. Methods Data from the open-label extension periods of the BLISS-52 and BLISS-76 trials of belimumab in SLE (NCT00724867; NCT00712933) were used (N = 973). FHS was defined as an experience of “no problems” in all five EQ-5D dimensions. Organ damage was assessed annually using the Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) Damage Index (SDI). Associations between the three-level version of the EQ-5D (EQ-5D-3L) responses at open-label baseline and the first documented increase in organ damage were investigated using Cox regression accounting for age, sex, ancestry, SDI at baseline, and background therapy, and associations with SDI items were investigated using phi (φ) correlation analyses. Results A total of 147 patients (15.1%) accrued organ damage during follow-up, with the first increase in their SDI score occurring after a mean time of 29.1 ± 19.6 months. Lower proportions of FHS respondents accrued damage over a course of up to 7.9 years of open-label follow-up compared with no FHS respondents (p = 0.004; derived from the logrank test). FHS was associated with a reduced hazard to accrue subsequent organ damage (HR: 0.60; 95% CI: 0.38–0.96; p = 0.033) after adjustments, as was experience of “no problems” in mobility (HR: 0.61; 95% CI: 0.43–0.87; p = 0.006). “No problems” in mobility was negatively correlated with musculoskeletal damage accrual (φ = −0.08; p = 0.008) and associated with a lower hazard to accrue musculoskeletal damage in Cox regression analysis (HR: 0.38; 95% CI: 0.19–0.76; p = 0.006). Conclusion Experience of EQ-5D-3L FHS and “no problems” in mobility after therapeutic intervention heralded reduced hazard to accrue subsequent organ damage, especially musculoskeletal damage, suggesting that optimisation of these health-related quality of life aspects constitutes a clinically relevant treatment target in patients with SLE, along with clinical and laboratory parameters.